Effects of preoperative aspirin use on mortality in Coronary Artery Bypass grafting patients - M Abbaszadeh; A Rabbani; MH Mandegar; E Jazayeri (Tehran University of Medical Sciences, 2008)
Background and Aim: Discontinuing aspirin use in patients before coronary artery bypass grafting (CABG) has focused on bleeding risks. The aim of this study was to determind the effect of aspirin use on overall mortality with this procedure. Materials and Methods: In a retrospective review was under taken of 2,252 consecutive isolated coronary artery bypass grafting (CABG) procedures performed between July 1995 and May 3003 in Tehran, Shriati hospital. Patients who had isolated CABG operations and received aspirin were analyzed and compared to nonusers undergoing similar bypass procedures during the same period. Aspirin use was defined by identification of ingestion within 7 days before the operation. Results: CABG patients using preoperative aspirin were less likely to experience in hospital hemorrhage compared to nonusers (P=0.0001). Significant difference was seen for transfusion of blood products, and need for reexploration for hemorrhage between patients who did and did not receive aspirin (P=0.0001).Mortality in multivariate (odds ratio [OR] =0.12, 95%confidence interval [0.05, 0.28] analysis was less to patients using aspirin compared to nonusers (p=0.0001). Conclusions : Preoperative aspirin use appears to be associated with a decreased risk of mortality in CABG patients with significant increase in hemorrhage, blood product requirements, or related morbidities.